Reducing the Cost of Medicaid: A Multistate Simulation. (November 2018) - Linder, Stephen H; Aguillard, Kimberly; French, Kelsey; Garson, Arthur
According to some estimates, the United States wastes as much as 30% of health care dollars. Some of that waste can be mitigated by reducing certain costs associated with Medicaid. We chose 5 areas of savings applicable to Medicaid: (1) modification of physician payment models to reduce unnecessary care, (2) development of a medication adherence program for patients dually eligible for Medicaid and Medicare support ("dual eligibles"), (3) improvement in unnecessary admissions and readmissions for dual eligibles, (4) reduction in emergency department visits among children in Medicaid and dual-eligible beneficiaries, and (5) improvement in adoption of end-of-life advance directives. We chose the states from both ends of the spending spectrum: the 5 with the lowest annual Medicaid expenditures: Wyoming, South Dakota, Montana, Vermont, and Alaska, and those with the highest: California, New York, Texas, Pennsylvania, and Florida. This spectrum demonstrates the range of potential cost-saving measures, from US 23.6 million in Wyoming to US 3.4 billion in California. We conclude that there are a number of ways to reduce Medicaid spending and improve quality. To the extent that states have already adopted programs addressing the same problems, our approach may be supplementary but the total savings may be achieved with a combination of current initiative and those described here. As Medicaid creates savings, physician payment could be increased to attract more physicians into caring for Medicaid patients.